Understanding the tampon density and density gradient through computed tomography imaging. Issue 6 (April 2016) - Hou, Mari; Acton, Paul D
Protection against leakage is one of the key consumer needs for tampon products. The absorbency of tampons depends on both the density of material inside the device, and the density gradient which pulls fluid into the core. Measuring tampon densities in a non-destructive manner was achieved using high-resolution three-dimensional computed tomography (CT) imaging. X-ray density was converted to mass density, using imaging of fiber pellets of known density. Two tampon types were scanned, and density and density gradients were calculated in both regions of interest and voxel-by-voxel. The CT scan density data were used to explain the results from a consumer use study that indicated a higher density prototype resulted in higher leakage versus a commercially available product that had a lower density profile at the periphery of the tampon and a higher density at its core.